Plastic Antibodies for Cosmetics: Molecularly Imprinted Polymers Scavenge Precursors of Malodors. (8th April 2016) - Nestora, Sofia; Merlier, Franck; Beyazit, Selim; Prost, Elise; Duma, Luminita; Baril, Bérangère; Greaves, Andrew; Haupt, Karsten; Tse Sum Bui, Bernadette
Abstract: Molecularly imprinted polymers (MIPs) are synthetic antibody mimics capable of specific molecular recognition. Advantageously, they are more stable, easy to tailor for a given application and less expensive than antibodies. These plastic antibodies are raising increasing interest and one relatively unexplored domain in which they could outplay these advantages particularly well is cosmetics. Here, we present the use of a MIP as an active ingredient of a cosmetic product, for suppressing body odors. In a dermo‐cosmetic formulation, the MIP captures selectively the precursors of malodorous compounds, amidst a multitude of other molecules present in human sweat. These results pave the way to the fabrication of a novel generation of MIPs with improved selectivities in highly complex aqueous environments, and should be applicable to biotechnological and biomedical areas as well.